1982
DOI: 10.1159/000182425
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Retinol and Retinol Binding Protein Concentrations in Patients on Maintenance Haemodialysis with and without Vitamin A Supplements

Abstract: Plasma retinol and retinol-binding protein (RBP) concentrations have been estimated in patients on maintenance haemodialysis over a 4-year period. For the first 2 years multivitamin supplements containing vitamin A were taken, and for the second 2 years no vitamin A supplements were given. Mean plasma retinol concentrations decreased significantly but only from 3.8 times normal to 3.1 times normal after vitamin A supplements stopped. There was no significant change in the high plasma RBP levels. Ultracentrifug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
(15 reference statements)
1
16
0
Order By: Relevance
“…Finally, as a number of biomarkers are known to be elevated in CKD without an apparent physiological effect [28], it may be that altered or inactive RBP metabolites interfere with our assay and contribute to the findings of the present study. However, a previous study has shown a strong correlation between retinol, RBP and retinol bound to RBP [24]. While these caveats mean that future experiments are needed both to verify the current report but also to better characterize and understand the mechanisms involved, the present study supports a role for RBP in uremic dysmetabolism.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Finally, as a number of biomarkers are known to be elevated in CKD without an apparent physiological effect [28], it may be that altered or inactive RBP metabolites interfere with our assay and contribute to the findings of the present study. However, a previous study has shown a strong correlation between retinol, RBP and retinol bound to RBP [24]. While these caveats mean that future experiments are needed both to verify the current report but also to better characterize and understand the mechanisms involved, the present study supports a role for RBP in uremic dysmetabolism.…”
Section: Discussionsupporting
confidence: 64%
“…Finally, serum RBP has also been shown to be expressed in adipose tissue [1, 23], especially in visceral fat [23]. While multiple factors likely contribute to the lack of any correlation between RBP and fat in some studies, it is especially noteworthy that RBP levels in the circulation are strongly influenced by retinol, and thus by renal function [24], which may be one explanation for why many of our observed correlations became more prominent following adjustment for serum retinol levels in a subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that RBP4 is consistently elevated in end-stage renal disease (ESRD) patients, who show 3.5-5 times the normal serum RBP4 concentrations (Farrington et al, 1981;Stewart and Fleming, 1982;Vahlquist et al, 1982;Blumberg et al, 1983). Ziegelmeier et al (2007) showed that patients undergoing chronic hemodialysis have 4-fold higher mean serum RBP4 levels than control subjects with glomerular filtration rates > 50 mL/min.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CRF show marked clinical signs of hypervitaminosis A toxicity [15] such as skin fragility, pruritus, xerosis, pigmentation, and hair loss suggesting altered ROL uptake by the skin. CRF serum analysis per formed previously by others showed alteration of the stoi chiometry of RBP and ROL, indirectly suggesting that apo-RBP might circulate in higher concentrations than in normal serum [16], Since the ratio of serum apo-to ROL-RBP might modify tissular uptake of ROL by RBP mem brane receptors, the levels of apo-and ROI.-RBP were analyzed by direct methods in CRF serum [unpubl.…”
Section: Introductionmentioning
confidence: 99%